2022
DOI: 10.1167/iovs.63.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Binocularly Asymmetric Crowding in Glaucoma and a Lack of Binocular Summation in Crowding

Abstract: Purpose Glaucoma is associated with progressive loss of retinal ganglion cells. Here we investigated the impact of glaucomatous damage on monocular and binocular crowding in parafoveal vision. We also examined the binocular summation of crowding to see if crowding is alleviated under binocular viewing. Methods The study design included 40 individuals with glaucoma and 24 age-similar normal cohorts. For each subject, the magnitude of crowding was determined by the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 85 publications
3
20
1
Order By: Relevance
“…A recent study done by our group also demonstrated an enlarged crowding zone in the parafoveal vision (i.e. 2 degrees and 4 degrees eccentricities) of patients with glaucoma compared with age-matched healthy controls ( Shamsi, Liu, & Kwon, 2022 ). Furthermore, comparing the crowding zone between the worse and the better eyes of patients with glaucoma indicated that eyes with more severe glaucomatous damage have a larger crowding zone, further highlighting the impact of glaucomatous damage on crowding.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…A recent study done by our group also demonstrated an enlarged crowding zone in the parafoveal vision (i.e. 2 degrees and 4 degrees eccentricities) of patients with glaucoma compared with age-matched healthy controls ( Shamsi, Liu, & Kwon, 2022 ). Furthermore, comparing the crowding zone between the worse and the better eyes of patients with glaucoma indicated that eyes with more severe glaucomatous damage have a larger crowding zone, further highlighting the impact of glaucomatous damage on crowding.…”
Section: Introductionsupporting
confidence: 57%
“…The average crowding zone for the three groups was compared at the foveal (<0.25 degrees eccentricity), parafoveal (2 degrees and 4 degrees eccentricities), and peripheral (8 degrees and 10 degrees eccentricity) retinal locations. Values of crowding zone for glaucoma and old healthy subjects were reported in studies by Shamsi et al ( Shamsi, Liu, & Kwon, 2022 ; 2 degrees and 4 degrees eccentricity) and Ogata et al ( Ogata et al, 2019 ; 10 degrees eccentricity). For old versus young normally sighted subjects, the crowding zone data were obtained from a study by Liu et al ( Liu et al, 2017 ; 2 degrees, 4 degrees, and 8 degrees eccentricities).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations